Risk factors for childhood malnutrition in Roma settlements in Serbia - Janevic Teresa; Petrovic Oliver; Bjelic Ivana; Kubera Amber (BMC, 2010)
Abstract Background Children living in Roma settlements in Central and Eastern Europe face extreme levels of social exclusion and poverty, but their health status has not been well studied. The objective of this study was to elucidate risk factors for malnutrition in children in Roma settlements in Serbia. Methods Anthropometric and sociodemographic measures were obtained for 1192 Roma children under five living in Roma settlements from the 2005 Serbia Multiple Indicator Cluster Survey. Multiple logistic regression was used to relate family and child characteristics to the odds of stunting, wasting, and underweight. Results The prevalence of stunting, wasting, and underweight was 20.1%, 4.3%, and 8.0%, respectively. Nearly all of the children studied fell into the lowest quintile of wealth for the overall population of Serbia. Children in the lowest quintile of wealth were four times more likely to be stunted compared to those in the highest quintile, followed by those in the second lowest quintile (AOR = 2.1) and lastly by those in the middle quintile (AOR = 1.6). Children who were ever left in the care of an older child were almost twice as likely to stunted as those were not. Children living in urban settlements showed a clear disadvantage with close to three times the likelihood of being wasted compared to those living in rural areas. There was a suggestion that maternal, but not paternal, education was associated with stunting, and maternal literacy was significantly associated with wasting. Whether children were ever breastfed, immunized or had diarrhoeal episodes in the past two weeks did not show strong correlations to children malnutrition status in this Roma population. Conclusions There exists a gradient relationship between household wealth and stunting even within impoverished settlements, indicating that among poor and marginalized populations socioeconomic inequities in child health should be addressed. Other areas on which to focus future research and public health intervention include maternal literacy, child endangerment practices, and urban settlements.